The English school and order: the case of association of Southeast Asian Nations (ASEAN) - Durmaz, Ferhat; Ra'ees, Wahabuddin; Hossain, Ishtiaq (IIUM Press, International Islamic University Malaysia, 2019)
The English School (ES) analytical framework concerning the formation of order in international relations posits that states establish order through rules and institutions within the framework of common interests and values to protect against anarchy. State-centred orders with limited civil society cooperation are pluralistic, while their converse (with a larger role for non-state actors) are solidarist. The Association of Southeast Asian Nations (ASEAN) was established in 1967 by Malaysia, Thailand, the Philippines, Singapore, and Indonesia based on common interests, such as strengthening sovereignty and creating stable relations in the face of anarchic problems like communism and internal instability. In numerous conventions ASEAN has adopted various norms, such as respect for the sovereignty of the states, the rule of law, non-use of power, peaceful resolution of disputes, and non-interference in other states. All these norms showed that the primary purpose of ASEAN is to protect state sovereignty and interests and to establish peaceful regional relations. The fact that state sovereignty is at the forefront, with limited cooperation of non-state actors, shows that the ASEAN regional order is pluralist. This article analyses the emergence and appearance of the ASEAN regional order (the unit of analysis) in the context of the ES (the theoretical framework).****************** Rangka kerja analitikal Sekolah Inggeris (ES) berkenaan dengan pembentukan perintah dalam perhubungan antarabangsa memaparkan bahawa negeri-negeri membentuk perintah melalui peraturan dan institusi-institusi dalam rangka kerja melibatkan yang minat umum dan nilai-nilai demi melindunginya daripada anarki. Perintah berpusatkan negeri dengan kerjasama masyarakat sivil terhad adalah dianggap pluralistik. Disebaliknya, mereka yang bukan pegawai kerajaan panggil sebagai satu perpaduan. Pertubuhan Bangsa-bangsa Asia Tenggara (ASEAN) telah ditubuhkan pada tahun 1967 dengan Malaysia, Thailand, Filipina, Singapura dan Indonesia dengan berlandaskan minat umum, seperti mengukuhkan kedaulatan dan mewujudkan hubungan yang stabil dalam menghadapi masalah anarki seperti komunisme dan dengan ketidakstabilan dalaman. Konvensyen ASEAN kebanyakan telah menerima pelbagai norma-norma seperti menghormati kedaulatan negara masing-masing, kedaulatan undang-undang, tidak menggunakan kuasa paksaan, penyelesaian perselisihan secara damai, dan tiada campur tangan dalam hal negara-negara lain. Kesemua norma-norma tersebut menunjukkan bahawa tujuan utama ASEAN adalah untuk melindungi kedaulatan negara demi kepentingan untuk mewujudkan hubungan serantau yang damai. Hakikatnya adalah bahawa kedaulatan negara berada di barisan hadapan. Dengan kerjasama yang terbatas, pegawai bukan kerajaan telah menunjukkan bahawa perintah serantau ASEAN adalah pluralis. Artikel ini menganalisis kemunculan dan penampilan perintah serantau ASEAN (unit analisis) dalam konteks ES (rangka kerja teoritis).